Applications of Hybrid Polymers Generated from Living Anionic Ring Opening Polymerization - Goff, Jonathan (Molecules, 2021)
Increasingly precise control of polymer architectures generated by “Living” Anionic Ring-Opening Polymerization (Living AROP) is leading to a broad range of commercial advanced material applications, particularly in the area of siloxane macromers. While academic reports on such materials remain sparse, a significant portion of the global population interacts with them on a daily basis—in applications including medical devices, microelectronics, food packaging, synthetic leather, release coatings, and pigment dispersions. The primary driver of this increased utilization of siloxane macromers is their ability to incorporate the properties of silicones into organic structures in a balanced manner. Compared to organic polymers, the differentiating properties of silicones—low T(g), hydrophobicity, low surface energy, and high free molal space—logically lend themselves to applications in which low modulus, release, permeability to oxygen and moisture, and tactile interaction are desired. However, their mechanical, structural and processing properties have until recently precluded practical applications. This review presents applications of “Living” AROP derived polymers from the perspective of historical technology development. Applications in which products are produced on a commercial scale—defined as not only offered for sale, but sold on a recurrent basis—are emphasized. Hybrid polymers with intriguing nanoscale morphology and potential applications in photoresist, microcontact printing, biomimetic soft materials, and liquid crystals are also discussed. Previously unreported work by the authors is provided in the context of this review.